ANALISIS KANDUNGAN KOLESTEROL TELUR BURUNG PUYUH (Coturnix coturnix japonica) YANG DIBERIKAN PAKAN KOMERSIAL DENGAN PENAMBAHAN TEPUNG RUMPUT LAUT - Adrian Akerina (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2021)
This study aims to determine the effect of cholesterol content of quail egg which is given commercial feed with the addition of seaweed flour which includes parameters: feed consumption, egg production, egg mass, feed conversion, and egg yolk cholesterol levels. This study used 160 female quails aged 5 weeks. The design used in this study used a completely randomized design with 4 treatments and 4 replications. Feeding with the addition of red seaweed flour can reduce feed consumption, egg production and feed conversion but feed with the addition of red seaweed flour also results in an increase in cholesterol content in quail egg yolks. Feeding with the addition of green and brown seaweed flour can minimize the cholesterol content in quail eggs but numerically, feed with the addition of green seaweed flour tends to produce quail egg yolks with lower cholesterol content compared to other treatments